2018
DOI: 10.3389/fphar.2018.00678
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of the Quality and the Design of Evaluations of Mobile Health, Telehealth, Smart Pump and Monitoring Technologies Performed in a Pharmacy-Related Setting

Abstract: Background: There is currently a need for high quality evaluations of new mobile health, telehealth, smart pump and monitoring technologies undertaken in a pharmacy-related setting. We aim to evaluate the use of these monitoring technologies performed in this setting.Methods: A systematic searching of English articles that examined the quality and the design of technologies conducted in pharmacy-related facilities was performed using the following databases: MEDLINE and Cumulative index to Nursing and Allied H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 78 publications
0
15
0
1
Order By: Relevance
“…However, these systems are very much in their infancy, and experience is limited. Baines et al ( 2018 ) have found that the numbers, design and quality of evaluation studies of these technologies are such that it is not possible at present to understand fully the benefits of these technologies, and for pharmacists to make appropriate decisions about their adoption. Baines et al point out that these technologies need considerable funding yet “despite the improvements in technology, there is limited evidence on how this translates to real settings and to consumer satisfaction.” It is likely that, due to the need for funding and adequate benefits assessment, the adoption of future technologies will need to be facilitated with a high level of intentionality by pharmacies, health service managers and policy-makers, if they are to be successful.…”
Section: Implications For Policy Makersmentioning
confidence: 99%
“…However, these systems are very much in their infancy, and experience is limited. Baines et al ( 2018 ) have found that the numbers, design and quality of evaluation studies of these technologies are such that it is not possible at present to understand fully the benefits of these technologies, and for pharmacists to make appropriate decisions about their adoption. Baines et al point out that these technologies need considerable funding yet “despite the improvements in technology, there is limited evidence on how this translates to real settings and to consumer satisfaction.” It is likely that, due to the need for funding and adequate benefits assessment, the adoption of future technologies will need to be facilitated with a high level of intentionality by pharmacies, health service managers and policy-makers, if they are to be successful.…”
Section: Implications For Policy Makersmentioning
confidence: 99%
“…Most technology driven systems required significant funding and support, particularly those involving latest technology. Rigorous comparative studies are needed to evaluate the effectiveness of different technologies ( Baines D.L. et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…To that end, ASHP and the ASHP Research and Education Foundation sponsor the Practice Advancement Initiative (PAI) ( American Society of Health-System Pharmacists, 2018 ). The goal of this initiative is to significantly advance the health and well-being of patients by supporting futuristic practice models that support the most effective use of pharmacists as direct patient care providers ( Baines D.L. et al, 2018 ).…”
Section: How Has This Transformed Pharmacy Practice In Hospitals?mentioning
confidence: 99%
“…These technology definitions all include the wider dynamic surrounding the use of technologies to include the actions of humans using clinical procedures and health systems to help create wellbeing and quality of life. In response, pharmacists would benefit from viewing technologies as embedded in, and inseparable from, the overall production processes that supply drugs and generate patient wellbeing (Baines et. al., 2018b).…”
Section: Health Technologymentioning
confidence: 99%